Beginning Microsoft Excel 2010. Part 3 - Megel, Yu. Ye.; Kovalenko, S. M.; Chaly, I. V.; Mikhnova, E. D. (Kharkiv Petro Vasylenko National Technical University of Agriculture, 2016)
Methodological guidelines are intended to assist students in studying Informatics in English, both in the classroom and individually.
Keywords: methodological guidelines; formulas; nested functions; information technologies